Application of Make a Match Cooperative Learning Model in Counseling Models Courses to Increase Participation and Student Learning Outcomes - Abdul Munir; Miswanto Miswanto; Nurarjani Nurarjani (BIRCU, 2022)
This study aims to determine the application of the Make A Match cooperative learning model in counseling models courses to increase student participation and learning outcomes. This type of research is classroom action research (classroom action research) spiral model of Kemmis & McTaggart. The research subjects were 20 students of the Guidance and Counseling Study Program, FIP Unimed, Academic Year 2020. The data collection instruments used were participation observation sheets and learning outcomes tests. The data analysis technique is descriptive-qualitative. The results of this study indicate that at the first meeting of the first cycle, the average percentage of participation sub-indicators was 76.54%, and increased at the second meeting of the first cycle to 77.69%. Furthermore, at the first meeting of the second cycle, it increased to 83.46% and increased again at the second meeting of the second cycle to 86.15%. The average sub-indicator of student participation in the first cycle reached 77.12% and increased in the second cycle to 84.18%. The increase in the average sub-indicator of cycle I to cycle II was 8.46 %. Followed by an increase in student learning outcomes seen from the increase in the percentage of student learning outcomes that achieve completeness, namely the results of the pre-test, no student achieves complete learning. Furthermore, student learning outcomes in the first cycle of 70.75 and in the second cycle of 84.50. The increase between cycles I and II was 13.75. In the first cycle, the number of students who have achieved completeness is 45%. In the second cycle increased by 100%. It can be concluded that the application of the make a match cooperative learning model can increase student participation and learning outcomes. This means that the hypothesis is accepted.